Tourism as leading sector for foreign exchange contributors with government policy efforts through visa-free visits in Bali - Pemayun, A.A. Gde Putra; Suryanata, I Gusti Ngurah Putra (International research journal of management, IT and social sciences, 2019)
The purpose of this study is to find out the visit visa-free policy can reach the target of tourist visits in Bali. Public policy is a series of interconnected choices (including decisions not to act) made by government bodies or officials, formulated in the fields of land, energy, and health to education, welfare, and crime. Policy implementation is the implementation of policies that have been formulated and lead to the results obtained in the form of the policy itself and the benefits that can be felt by the community so that the implementation of the policy needs to be studied more deeply. Implementation is an important aspect of the overall policy process that produces output. Visit visa-free policy is not the only major determinant that attracts foreign tourists to Bali, foreign tourists come to visit because the area is indeed interesting to visit, in line with this, the government is now beginning to exploit existing tourism potentials, encouraging participation active community and supporting with other facilities, however, the visit visa-free policy is an efficient and easy to implement program to achieve greater foreign tourist visits.